STUDY FOR THE INFLUENCE OF NEW DIAZINONE-4 DERIVATIVES AND THEIR ACYCLIC PREDECESSORS ON THE DYNAMICS OF WEIGHT AD MASS COEFFICIENTS OF RATS' ORGANS - A. V. Voronkov; S. A. Luzhnova; Suda Billel; S. A. Osychenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
According to foreign and Russian researchers a problem of anti-microbial drugs resistance today is not a future forecast but is a serious threat, since it is encounteredin every region of the world and is a risk of health for every person not depending on his age and place of living. Development of efficient and safe medicinal drugs with high antibacterial activity is one of the ways to solve the problem. New derivatives of 1,3-diazinon-4 and their acyclic predecessors exhibit antibacterial activity which conditions their perspective for further development. Toxicological studies are important element of the assessment of chemical compounds safety, considered as potentially perspective for the creation of new medicinal drugs. Particularly, the studies of integral indexes which reflect a dynamics of metabolism process in animal organism, such as their weight and mass coefficients of their organs. The purpose of the work is an estimation of the influence of 30-day administration course of PYATd1, PYATs2, PYATs4, PYATd12, PYATs3, PYATd8 on a general condition, weight dynamics and mass coefficients of the rats' organs. Materials and methods. The studies used 120 both gender Wistar rats weighed 190-210 g. Fourteen groups by 7-10 animals were formed. The compounds were injected through a probe into a stomach at dose 50 mg/kg once a day in the morning. Every day visual examination of animals was carried out during the compounds injection, and peculiarities of their actions were noted. On the 31st day, the animals were weighed, and then removed from the experiment by decapitation using anesthesia (intraabdominal injection of hydrochloride at dose 350 mg/kg). Internals (heart, lungs, stomach, spleen, kidneys, liver, adrenals, brain) were extracted, weighed, and their mass coefficients were calculated. Results and discussion. The study conducted showed that 30-day administration of the compounds does not lead to pathologic weight loss and significant changes of mass coefficients of the animals'internals, which gives evidence about the absence of compounds' toxic influence on the organism.